Impact Beyond Financial Sustainability: A Review to Unravel Factors that Impact Sustainability Initiatives in MSMEs - Opoku Nkansah, Obed Kwabina; Gaffar, Vanessa; Sofia, Alfira (Image : Jurnal Riset Manajemen, 2024)
In developing countries, formal MSMEs provide up to 60% of all jobs and contribute up to 40% to the GDP (World bank,2015). The focus of MSMEs traditionally has been financial sustainability measured by revenue and profitability. Recent calls on MSMEs however have been the drive for sustainability initiatives. The study aimed at exploring the factors that influence sustainability initiatives globally. A systematic literature review was conducted using data bases such as EBSCO, EMERALD, Science Direct Scopus, Wiley Online and Google Schorlar resulting in 44 peer reviewed papers from 1990 to 2021. The study revealed diverse factors that influence sustainability, grouped into internal and external factors. A key factor that came to light in the review was the future embracement of state-of-the-art technology. Overall, the study provides important insights into the factors that can drive sustainability initiatives of MSMEs.